2018
DOI: 10.1021/acsomega.8b01940
|View full text |Cite
|
Sign up to set email alerts
|

Development of Thick Superhydrophilic TiO2–ZrO2 Transparent Coatings Realized through the Inclusion of Poly(methyl methacrylate) and Pluronic-F127

Abstract: A thick coating of hierarchically porous double-templated TiO 2 –ZrO 2 –PMMA–PF127 with excellent self-cleaning properties and high transmittance has been developed for the first time on glass substrates using a simple dip-coating technique. Comparative studies of this sample with a thick and transparent coating of single-templated TiO 2 –ZrO 2 –PMMA have been performed to probe the origin of its exceptional properties.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 50 publications
(99 reference statements)
0
21
0
Order By: Relevance
“…In a summary, FTIR study revealed the presence of polar functional groups like C=O, C-O, and O-C-O, which bring polarity onto molecules, thereby repelling the polar groups present in water, which in turn helps in improving the hydrophobicity of nanofibers, and oleophilicity toward oil during oil-water separation experiments [2,5,[8][9][10][11][12][13][14][15].…”
Section: Ftir Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…In a summary, FTIR study revealed the presence of polar functional groups like C=O, C-O, and O-C-O, which bring polarity onto molecules, thereby repelling the polar groups present in water, which in turn helps in improving the hydrophobicity of nanofibers, and oleophilicity toward oil during oil-water separation experiments [2,5,[8][9][10][11][12][13][14][15].…”
Section: Ftir Analysismentioning
confidence: 99%
“…The activated charcoal molecules exhibit functional groups like C=O, -CO 3 , O-H, and C-O which imparts polarity unto it, and the effect of these polar charges probably becomes more pronounced when the activated charcoal molecules try to organize themselves in the polymer during fiber formation (stretching of polymer chains) in electrospinning process [2,5,[8][9][10][11][12][13][14][15], thereby helping improving the water repellency characteristics. Since the electrospinning process parameters are constant, the activated charcoal molecules at 1.5% loading get probably less space to relax and re-organize during fiber formation, as compared to PC + AC(0.5%), and PC + AC(1%) microfibers.…”
Section: Morphological Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…34 There are some works that, as an alternative to swelling, use voids on the surface to trap water and cause an effect of hydrophilicity and self-cleaning by a direct contact of external drops with the water already on the surface. 35 There are works related to the deposition of some layers on a swelling polymer that leads to the formation of uniform wrinkles after the release of polymer strain because of isotropic polymer elongation. Particularly, conductive silver wrinkles have been grown on an elastomer by combining polymer swelling with electroless deposition for ultrasensitive pressure sensors.…”
Section: Introductionmentioning
confidence: 99%